The AMA handbook of public relations. - Dilenschneider, Robert L. 4 0 16; 5 (New York : AMACOM, 2010)
Describes how to create powerful campaigns and expand public relations by integrating traditional media with twenty-first-century Web-based communications.
Includes bibliographical references (p. 225-226) and index.
Publisher's Weekly, February 2010;Publisher's Weekly
Keywords: 2 -- 0; 6; Public relations.;Public relations;Public relations.;Public relations -- United States.;United States; 20; 2